Serial Quantitative Evaluation of Load Redistribution and Osteotomy Gap After Medial Open‐Wedge High Tibial Osteotomy - Cho, Jae Woo; Song, Yoo Sung; Park, Se Jin; Lee, Won Woo; Lee, Yong Seuk (Journal of orthopaedic research, 2025)
ABSTRACT The goal of medial open‐wedge high tibial osteotomy (MOW‐HTO) is to redistribute load by realigning the lower limb. This surgery is indicated for mild to moderate medial compartment osteoarthritis with varus deformity in cases unresponsive to conservative treatment. Procedures for accompanying cartilage lesions, such as multiple drilling on the medial femoral condyle (MFC), are often performed simultaneously, potentially affecting bone metabolism along with load redistribution and union progression. This study assessed changes in bone metabolism following MOW‐HTO. Two‐year follow‐up data were collected from 51 knees undergoing MOW‐HTO between March 2019 and December 2020. Single‐photon emission computed tomography and conventional CT (SPECT/CT) were performed on postoperative Day 1, 3 months, 1 year, and 2 years. Maximum standardized uptake value (SUVmax) was measured in each compartment and the osteotomy gap. At 1 year postoperatively, SUVmax decreased in the medial femur and tibia zones (p < 0.001). SUVmax decreased in the lateral osteotomy gap zones at 1 year (p = 0.001 anterior; p = 0.002 posterior), while medial zones showed a sustained increase. At the posteromedial zone, SUVmax decreased at 2 years (p = 0.012). Subjects were divided into two groups: those with MFC drilling (group one) and those without (group two). SUVmax was higher in group one throughout the 2 years (p < 0.001). Unloading effects were notable in the medial compartment. MFC drilling increased SUVmax, creating different patterns between groups. SUVmax decrease in the osteotomy gap occurred earlier in the lateral zone.